Q: 23 plus 46 - 25 equals?

Write your answer...

Submit

Still have questions?

Related questions

27 times 3 minus 46 plus 23 equals 58.

658

It's 46. 23 times 2 equals 46

The sum of 23 and 46 is 69

46 + 25 = 71

2a + 2b = 26 2b + c = 22 ===> b = 11 - c/2 4c + 2b = 46 ===> b = 23 - 2c From the 2nd and 3rd equations: 11 - c/2 = 23 - 2c 22 - c = 46 - 4c 22 - 46 = -4c + c ===> -24 = -3c ===> c = 8 Substitute c=8 into the 3rd equation: b = 23 - 16 = 7 Substitute b=7 into the 1st equation: 2a + 14 = 26 2a = 12 ===> a = 6

1, 2, 23, 46: (1 x 46, 2 x 23)

ur answer is t= -23 -23 x 3= -69 + 46 = -23

It is 134+46 = 180

46 = 1 x 46, 2 x 23, 23 x 2, 46 x 1.

23 x 2 = 46

123